2008
DOI: 10.1007/978-3-540-75261-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Engineering of Complex Functional Networks

Abstract: Complex biological networks are responsible for many fundamental processes in living organisms, including signal transduction and genetic expression in biological cells and signal processing in neural networks. These functional networks, a product of the evolution, are characterized by their robustness against damages, mutations and noise. Functionality and robustness are reflected in their architectures which exhibit structures different from random networks and lattices.To design functional networks, robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Two mutation schemes have been tried [10]. In the link mutation scheme, a mutation consists in adding a new connection or deleting an existing one from the network.…”
Section: Return To Stepmentioning
confidence: 99%
See 3 more Smart Citations
“…Two mutation schemes have been tried [10]. In the link mutation scheme, a mutation consists in adding a new connection or deleting an existing one from the network.…”
Section: Return To Stepmentioning
confidence: 99%
“…The constructive approach for studies of bionetworks has been followed in our recent publications [6][7][8]. Using a simplified model representing an abstraction of biological signal processing, ensembles of networks with the same output functions have been generated, which were additionally designed to be self-correcting against deletion of individual links or nodes, or against the application of distributed quenched noise.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These results could be further extended to flow network models with dynamic responses [7]. For coupled phase oscillators, it was shown that, by running evolutionary optimization, networks that are better entrained by pacemakers could be designed [8,9].…”
Section: Introductionmentioning
confidence: 95%